Brief Report: Bullying and Anxiety in High-Functioning Adolescents with ASD - van Schalkwyk, Gerrit; Smith, Isaac C.; Silverman, Wendy K.; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Youth with ASD are more likely to experience bullying than their typically developing peers. This risk has not been studied in youth with ASD transitioning to college. We examined the occurrence of bullying in 35 high functioning youth with ASD who were preparing to attend college. We also examined youth anxiety and ASD symptoms. Fifty-one percent of the sample reported being recent victims of bullying; 31% of parents reported their child was a victim of bullying. Parent report of bullying correlated significantly with ratings of youth social anxiety symptoms. These findings suggest that bullying is an issue of concern for higher functioning, older adolescents with ASD, and that their own reports may be particularly important in identifying its occurrence.
Keywords: Anxiety; Autism spectrum disorder; Bullying; Postsecondary education; dept.sed

Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

A professional development training model for improving co-teaching performance - Faraclas, K.L. (International Journal of Special Education, 2018)
Co-teaching is a promising practice for educating students with disabilities in regular education classes. However, teachers often report being given co-teaching assignments without requisite training. Without adequate preparation, many teachers have difficulty conceptualizing coteaching as a model and working collaboratively as teaching partners, often creating a division of labor that relegates special educators to a "helper" role in the classroom. This experimental study utilized a randomized pretest-posttest control group design to study the effects of a professional development training package on the collaborative teaching performance of regular and special education teachers. Analysis of covariance showed that teachers who participated in professional development training on co-teaching had significantly higher posttest scores on a co-teaching performance assessment than those who did not participate in training. © 2019, International Journal of Special Education. All rights reserved.
Keywords: Co-teaching; Collaboration; Effective teaching; Inclusion; Professional development; Research; Special education; Students with disabilities; Teacher education; Teacher training; dept.sed; peer-reviewed; ⛔ No DOI found

Book Review: Joseph Dorinson: Kvetching and Shpritzing: Jewish Humor in American Popular Culture : view - Saltman, J.M. (Humor, 2018)
0 citations (Crossref) [2023-10-31] ISBN: 09331719 (ISSN) Publication Title: Humor
Keywords: book.review; dept.sed

Can we get there from here? Learning disabilities and future edueation poliey - Spear-Swerling, L. (Perspectives on Learning Disabilities: Biological, Cognitive, Contextual, 2018)
Contemporary educational policies for identifying learning disabilities (LD) have been widely criticized. I would like to begin this chapter with a story that illustrates some of the conundrums in these policies. © 1999 Taylor & Francis.
Journal Abbreviation: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual
Keywords: dept.sed

Perspectives on learning disabilities: Biological, cognitive, contextual - Sternberg, R.J.; Spear-Swerling, L. (Taylor and Francis, 2018)
This book discusses biological, cognitive, educational, sociological, and interactive to discuss the nature of learning disabilities, its origins, its diagnosis, and effective remediation. It emphasizes the development of ideas as the motor forces behind the economic policies. © 1999 Taylor & Francis.
Journal Abbreviation: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual Pages: 296 Publication Title: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual
Keywords: dept.sed

Preface - Sternberg, R.J.; Spear-Swerling, L. (Perspectives on Learning Disabilities: Biological, Cognitive, Contextual, 2018)
Keywords: dept.sed; ⛔ No DOI found

Coteaching in content area classrooms: Lessons and guiding questions for administrators - Sinclair, Anne C.; Bray, Laura E.; Wei, Yan; Clancy, Erin E.; Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J. (NASSP Bulletin, 2018)
Secondary school administrators increasingly include students with disabilities in general education classrooms with coteaching models. Theoretically, coteaching enables two educators to attend to the learning needs of students with disabilities while exposing them to grade-level content area instruction. However, our study on teachers’ perceptions of coteaching found that teachers often viewed their schools’ leadership decisions as adversely affecting their ability coteach effectively. The purpose of this article is to provide administrators with an overview of common coteaching models, summarize findings from our study on teachers’ perceptions of how their schools’ leadership influenced their coteaching practices, and provide a set of guiding questions to consider when seeking to support coteaching. © 2018 SAGE Publications.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-514-925-194-03X, pop00123 tex.type: [object Object]
Keywords: coteaching; dept.rdg; dept.sed; inclusion; instructional leadership; peer-reviewed; professional development

Brief article of gratitude to Paul McGhee - Saltman, Joyce (Humor-International Journal of Humor Research, 2018)
0 citations (Crossref) [2023-10-31] tex.eissn: 1613-3722 tex.unique-id: ISI:000431127000005
Keywords: dept.sed; peer-reviewed

A high school replication of targeted professional development for classroom management - Freeman, Jennifer; Kowitt, Jennifer; Simonsen, Brandi; Wei, Yan; Dooley, Kate; Gordon, Lola; Maddock, Eleanor (Remedial and Special Education, 2018)
In areas of emerging research, such as supporting teachers' classroom management, replication of research is critical to ensuring that recommendations for the field are based on sound science and appropriate for the contexts to which they are being applied. This article describes a replication of research on efficient professional development supports for teachers' classroom managements in a new context: high school classrooms. Data did not support a functional relation between teachers' use of specific praise and the targeted professional development and self-management in the high school setting. Results of this study highlight the critical importance of replication in education research. Based on our findings and our experience conducting this study, we suggest several possible adaptations may be necessary for successful replication at the high school level.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-228-318-057-658, pop00145 tex.type: [object Object]
Keywords: behavior; dept.rdg; dept.sed; inservice training; management; peer-reviewed; personnel preparation; research methodology; secondary; single-subject; staff development/inservice

Reading comprehension and co-teaching practices in middle school English language arts classrooms - Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J.; Mitchell, Marisa; Clancy, Erin; Davidson, Kimberly A.; Sinclair, Anne C.; Wei, Yan (Exceptional Children, 2018)
This study reports practices implemented in over 2,000 minutes by 16 middle school special education and general education co-teaching pairs in English language arts classes. We report the extent to which teachers integrated literacy activities that support reading comprehension, the co-teaching models used, and the frequency with which each teacher led instruction. We also report the types of grouping structures teachers used and the extent to which teachers interacted with students with disabilities. Finally, we report the types of text used. Observations revealed that more than half of time spent on literacy activities involved reading aloud or silently with no co-occurring literacy instruction that supports reading comprehension. Students with disabilities spent a majority of their time in whole-class instruction or working independently with little teacher interaction. Special education teachers spent most of their time supporting whole-class instruction led by the content-area teacher. Implications and directions for future research are provided.
37 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-264-196-907-683, pop00086 tex.type: [object Object]
Keywords: dept.rdg; dept.sed; peer-reviewed

Higher education and disability: A systematic review of assessment instruments designed for students, faculty, and staff - Lombardi, Allison; Gelbar, Nicholas; Dukes, III, Lyman L.; Kowitt, Jennifer; Wei, Yan; Madaus, Joseph; Lalor, Adam R.; Faggella-Luby, Michael (Journal of Diversity in Higher Education, 2018)
In this study, the literature in disability and higher education was examined, with a specific focus on assessment instruments. Published articles (n = 203) on development of new or refinement of existing instruments were reviewed for traits measured and psychometric rigor reported. Findings showed instruments are intended for professionals and students, and of the student instruments, broad categories are academic, nonacademic, and specific to a disability diagnosis. Not all instruments are limited to students with disabilities; many of the reviewed instruments can be utilized in higher-education settings on all students, faculty, and staff, regardless of disability. The implications of the findings undergird the urgency to prioritize disability as a facet of diversity within higher-education scholarship, and furthermore aid this prioritization by providing a catalogue of robust instruments to researchers and practitioners.
25 citations (Crossref) [2023-10-31] tex.eissn: 1938-8934 tex.unique-id: ISI:000426973700003
Keywords: Disability; assessment; campus climate; dept.rdg; dept.sed; peer-reviewed; program evaluation

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
104 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Reading comprehension strategies in autism spectrum disorders - Bean, Kimberly (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed

The need for caregiver support for families of children with ASD - Bean, Kimberly; Meers, K (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed